Enhancing Pramuka Saka Bahari’s Role in Strengthening Indonesia’s Maritime Security - Nia Norlyanti (Jurnal Lemhannas RI, 2024)
Purpose: To optimise the role of Pramuka Saka Bahari in enhancing maritime security by examining its potential contributions to the defence system of the world’s largest archipelagic state, Indonesia, and addressing the urgency of integrating youth organisations into national maritime defence strategies. Study Design/Methodology/Approach: A qualitative methodology applied a systematic literature review to evaluate challenges, identify influencing factors, and propose strategies to enhance Pramuka Saka Bahari’s effectiveness. Data were sourced from peer-reviewed articles, policy documents, and reports published between 2010 and 2023. Findings: Pramuka Saka Bahari contributes to maritime security by fostering maritime awareness, providing navigation training, and promoting marine environmental education. It equips youth with essential skills to address traditional and non-traditional security threats. Challenges include resource constraints, limited coordination with maritime agencies, inadequate training programmes, and low public awareness. Strategies include developing a maritime security curriculum, improving inter-agency collaboration, implementing coastal surveillance initiatives, enhancing mentor training, and increasing public awareness through targeted campaigns. Originality/Value: Highlights the strategic importance of revitalising Pramuka Saka Bahari through integrated and innovative approaches. Recommendations aim to optimise its role in fostering a sustainable and inclusive maritime security framework, ensuring national sovereignty and resilience in the face of evolving maritime challenges.